Effectiveness of Constructivism Approach to Increase Mathematical Communication Skill of Students Junior High School - ., Hadijah; Puteh, Marzita (International Journal of Engineering and Technology, 2018)
The purpose of this study is to analyze and explore the effectiveness of constructivism approach in improving the mathematical communication skills of junior high school (SMP) in Paser city, Indonesia. Type of research used in this study are mix method (quantitative and qualitative) in form of pre test, post test, questionnaire and observation. The research method used in this research is quasi experimental method. In this study, the population is all high school students in Paser City and the sample study was VII class students at three junior high schools in Paser City, Furthermore from each of the schools selected 1 class as the treatment group and 1 class as the control group, so the total is 6 classes. In this research there are two types of data that are quantitative data and qualitative data. For quantitative data analysis and data processing using Statistical Package for Social Science (SPSS) Version 21.0. using the Levene Test is used to see the uniformity of treatment groups and control groups. Then Qualitative data is obtained from the observation process. For observations in descriptive analysis to support quantitative data completenessÂ